A study to assess the Quality of Life of Children’s with Acute Respiratory Tract Infections admitted in selected hospital , chennai. - R. Bindhiya; Dr. Sathiyalatha Sarathi; Dr. V. Hemavathy (The Bioscan, 2025)
Introduction: Acute Respiratory Tract Infections remain a significant concern in pediatric health care globally, contributing to high rates of hospitalization, morbidity, and mortality among children, particularly those under five years of age. Aim of the study: The main aim of the study to assess the Quality of Life of Children’s with Acute Respiratory Tract Infections admitted in selected hospital, Chennai. Methodology: This study adopted a descriptive research design to assess the Quality of Life (QoL) among children aged 6 to 12 years diagnosed with Acute Respiratory Tract Infections (ARTIs) and admitted to a selected tertiary care hospital in Chennai. A total of 80 children were selected using a convenience sampling technique based on admission availability and inclusion criteria. Children with chronic illnesses, immunocompromised conditions, or pre-existing psychological or neurological impairments were excluded. The design aimed to describe the QoL status and explore the influence of clinical and demographic factors. Result: The study revealed a moderate overall Quality of Life (QoL) score of 66.9 among children, with emotional functioning (72.4) being the highest and school functioning (60.3) the lowest. QoL was significantly associated with gender (p = 0.030), parental education (p = 0.045), socioeconomic status (p = 0.048), type of infection (p = 0.017), and hospital stay duration (p = 0.022), while age (p = 0.076) was not significant. Conclusion: The study concludes that children with acute respiratory infections demonstrated a moderate quality of life, with emotional well-being being the strongest domain and school functioning the weakest. Key factors influencing their quality-of-life included gender, parental education, socioeconomic status, type of infection, and length of hospital stay.